Functions of p38 MAP Kinases in the Central Nervous System - Asih, Prita R.; Prikas, Emmanuel; Stefanoska, Kristie; Tan, Amanda R. P.; Ahel, Holly I.; Ittner, Arne (Frontiers in Molecular Neuroscience, 2020)
Mitogen-activated protein (MAP) kinases are a central component in signaling networks in a multitude of mammalian cell types. This review covers recent advances on specific functions of p38 MAP kinases in cells of the central nervous system. Unique and specific functions of the four mammalian p38 kinases are found in all major cell types in the brain. Mechanisms of p38 activation and downstream phosphorylation substrates in these different contexts are outlined and how they contribute to functions of p38 in physiological and under disease conditions. Results in different model organisms demonstrated that p38 kinases are involved in cognitive functions, including functions related to anxiety, addiction behavior, neurotoxicity, neurodegeneration, and decision making. Finally, the role of p38 kinases in psychiatric and neurological conditions and the current progress on therapeutic inhibitors targeting p38 kinases are covered and implicate p38 kinases in a multitude of CNS-related physiological and disease states.